Differential Ventilation Using Flow Control Valves as a Potential Bridge to Full Ventilatory Support during the COVID-19 Crisis: From Bench to Bedside. (October 2020) - Levin, Matthew A.; Shah, Anjan; Shah, Ronak; Kane, Erica; Zhou, George; Eisenkraft, James B.; Chen, Martin D.; Katz, Daniel; Park, Chang; Lai, Cheuk Yin; Burnett, Garrett; Gidicsin, Christopher; et al.
Abstract : Background: During the COVID-19 pandemic, ventilator sharing was suggested to increase availability of mechanical ventilation. The safety and feasibility of ventilator sharing is unknown. Methods: A single ventilator in pressure control mode was used with flow control valves to simultaneously ventilate two patients with different lung compliances. The system was first evaluated using high-fidelity human patient simulator mannequins and then tested for 1 h in two pairs of COVID-19 patients with acute respiratory failure. Patients were matched on positive end-expiratory pressure, fractional inspired oxygen tension, and respiratory rate. Tidal volume and peak airway pressure (PMAX ) were recorded from each patient using separate independent spirometers and arterial blood gas samples drawn at 0, 30, and 60 min. The authors assessed acid-base status, oxygenation, tidal volume, and PMAX for each patient. Stability was assessed by calculating the coefficient of variation. Results: The valves performed as expected in simulation, providing a stable tidal volume of 400 ml each to two mannequins with compliance ratios varying from 20:20 to 20:90 ml/cm H2 O. The system was then tested in two pairs of patients. Pair 1 was a 49-yr-old woman, ideal body weight 46 kg, and a 55-yr-old man, ideal body weight 64 kg, with lung compliance 27 ml/cm H2 O versus 35 ml/cm H2 O. The coefficient of variation for tidal volume was 0.2 to 1.7%, and for PMAX 0 to 1.1%. Pair 2 was a 32-yr-old man, ideal body weight 62 kg, and a 56-yr-old woman, ideal body weight 46 kg, with lung compliance 12 ml/cm H2 O versus 21 ml/cm H2 O. The coefficient of variation for tidal volume was 0.4 to 5.6%, and for PMAX 0 to 2.1%. Conclusions: Differential ventilation using a single ventilator is feasible. Flow control valves enable delivery of stable tidal volume and PMAX similar to those provided by individual ventilators. Abstract : Custom three-dimensional printed inspiratory flow control valves designed to allow individualized setting of tidal volume and airway pressure were evaluated using high-fidelity simulator mannequins with similar or different lung compliance and were found to perform as expected with stable tidal volumes delivered to each mannequin. The system demonstrated stable performance when tested for 1 h in two pairs of volunteer COVID-19 patients with acute respiratory failure. Continuous assessment of tidal volume and peak airway pressure in each patient during the study allowed for dynamic alteration of tidal volume in response to respiratory acidosis. This study suggests that custom-designed flow control valves may facilitate the use of split ventilation techniques in a surge setting.Supplemental Digital Content is available in the text.